2009
DOI: 10.4269/ajtmh.2009.81.317
|View full text |Cite
|
Sign up to set email alerts
|

Intrascrotal Nodules in Adult Men as a Marker for Filarial Granuloma in a Bancroftian Filariasis-Endemic Area

Abstract: A retrospective study was undertaken in Recife, Brazil to evaluate the specificity of intrascrotal nodules detected by physical examination as a marker of dead or degenerating adult Wuchereria bancrofti worms (filarial granuloma). A total of 372 nodules from 340 adult male patients (mean age 23.1 years) were studied. Of those, 253 (68%) nodules were from 226 patients treated with antifilarial drugs (Group 1) and 119 (32%) nodules were considered non-drug related and were obtained from 114 patients (Group 2). O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…It is emphasized that the treatment with DEC for individuals when they present microfilaremia may be of fundamental importance for the control of transmission, highlighting the fact that these individuals continue to live in endemic areas, and are at risk of reinfection [ 36 ]. A retrospective study in Brazil emphasized that the best way to monitor the effectiveness of antifilarial drugs is the combined use of ultrasound and physical examination to monitor the development of scrotal nodules [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is emphasized that the treatment with DEC for individuals when they present microfilaremia may be of fundamental importance for the control of transmission, highlighting the fact that these individuals continue to live in endemic areas, and are at risk of reinfection [ 36 ]. A retrospective study in Brazil emphasized that the best way to monitor the effectiveness of antifilarial drugs is the combined use of ultrasound and physical examination to monitor the development of scrotal nodules [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Norões et al [7] demonstrated that, by contrast, acute filarial hydrocele is a consequence of acute interruption of lymph flow from the tunica vaginalis of the testis. This obstruction is caused by filarial granuloma (corresponding to formation of palpable nodules detected by physical examination of intrascrotal contents [15]) resulting from death of W. bancrofti adult worms in the lumen of intrascrotal lymphatic vessels. They observed that 22% of patients who experienced nodule formation also developed acute hydroceles, and reabsorption of the granuloma led to resolution of 76% of such acute hydroceles within seven months during an eighteen month follow up period.…”
Section: Discussionmentioning
confidence: 99%
“…In such scenarios, eosinophil degranulation is expected to occur, but no studies have specifically investigated this. In men, spontaneous or drug-induced adult W. bancrofti parasite death is followed by the development of a palpable nodule, most commonly localized in intrascrotal lymphatic vessels (21,22). The present study was undertaken to determine the immunohistochemical expression of MBP, EPO and ECP in granulomatous lesions in scrotal nodules removed from DEC-treated and non-treated patients.…”
Section: Introductionmentioning
confidence: 98%